The influence of learning motivation and student creativity on entrepreneurial interest in teaching factory - Susiani, Irna; Soeryanto, Soeryanto; Asto Buditjahjanto, I Gusti Putu; Anifah, Lilik (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2024)
This research aims to examine the influence of learning motivation and learning creativity on students' interest in entrepreneurship at Kartanegara Wates Vocational School, Kediri Regency in Teaching Factory learning. This type of research is quantitative research with 80 students as research subjects. The data collection technique for this research uses a questionnaire. The data analysis used in this research is multiple linear regression. The research results showed that the partial test (t-test) on learning motivation was .000 < .050 and for creativity, it was .00 < .050. Meanwhile, the results obtained from the F-test show a value of .000 < .050. The determination test results obtained a value of 53.7%. The findings in this research show that learning motivation has a significant effect on interest in entrepreneurship. Additionally, creativity also shows a significant influence on interest in entrepreneurship. Learning motivation and creativity simultaneously have a significant influence on the entrepreneurial interest of Kartanegara Wates Vocational School students.